The Change of Systemic Immune-Inflammation Index Independently Predicts Survival of Colorectal Cancer Patients after Curative Resection. (16th November 2020) - Chen, Qingqing; Wu, Haohao; Guo, Xinwei; Gu, Ke; Wang, Wenjie; Chen, Xiaochen; Ji, Shengjun; Yang, Hui; Zhu, Jiahao
Abstract : Background . The systemic immune-inflammation index (SII) has an important role in predicting survival in some solid tumors. However, little information is available concerning the change of the SII (∆SII) in colorectal cancer (CRC) after curative resection. This study was designed to evaluate the role of ∆SII in CRC patients who received surgery. Methods . A total 206 patients were enrolled in this study. Clinicopathologic characteristics and survival were assessed. The relationships between overall survival (OS), disease-free survival (DFS), and ∆SII were analyzed with both univariate Kaplan-Meier and multivariate Cox regression methods. Results . Based on the patient data, the receiver operating characteristic (ROC) optimal cutoff value of ∆SII was 127.7 for OS prediction. The 3-year and 5-year OS rates, respectively, were 60.4% and 36.7% in the high-∆SII group (>127.7) and 87.6% and 79.8% in the low-∆SII group (≤127.7). The 3-year and 5-year DFS rates, respectively, were 54.1% and 34.1% in the high-∆SII group and 80.3% and 78.5% in the low-∆SII group. In the univariate analysis, smoking, pathological stages III-IV, high-middle degree of differentiation, lymphatic invasion, vascular invasion, and the high- Δ SII group were associated with poor OS. Adjuvant therapy, pathological stages III-IV, vascular invasion, and Δ SII were able to predict DFS. Multivariate analysis revealed that pathological stages III-IV (HR = 0.442, 95% CI = 0.236 -0.827, p = 0.011 ), vascular invasion (HR = 2.182, 95% CI = 1.243 -3.829, p = 0.007 ), and the high- Δ SII group (HR = 4.301, 95% CI = 2.517 -7.350, p < 0.001 ) were independent predictors for OS. Adjuvant therapy (HR = 0.415, 95% CI = 0.250 -0.687, p = 0.001 ), vascular invasion (HR = 3.305, 95% CI = 1.944 -5.620, p < 0.001 ), and the high- Δ SII group (HR = 4.924, 95% CI = 2.992 -8.102, p < 0.001 ) were significant prognostic factors for DFS. Conclusions . The present study demonstrated that ∆SII was associated with the clinical outcome in CRC patients undergoing curative resection, supporting the role of ∆SII as a prognostic biomarker.